Titanium-zirconium alloy wire material for high-strength annealed implant and processing method of titanium-zirconium alloy wire material

By adopting three-time VAR smelting and roller mold hot-pull-cooling and pulling process, combined with specific heat treatment processes, titanium-zirconium alloy wire material for high-strength annealed implants was prepared, which solved the problems of insufficient strength and high price of existing dental implant materials, and achieved high strength, fatigue resistance and low cost domestic substitution.

CN119614919APending Publication Date: 2025-03-14BAOJI XINNUO NEW METAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411799472.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing dental implant materials are insufficient in mechanical strength and are prone to stress fatigue and fracture, which is difficult to meet the clinical needs of narrow-diameter implants and anterior dental implants. At the same time, the price is high, which limits the popularity of the market.

Method used

The deformation distribution process combined with three VAR smelting, roller mold hot pulling and cold pulling is adopted, and a specific heat treatment process is combined with a titanium-zirconium alloy wire for high-strength annealed implant is prepared to achieve stable room temperature tensile performance and tensile strength greater than or equal to 1000MPa.

Benefits of technology

It has achieved high strength and high stability of titanium-zirconium alloy wire, and is suitable for narrow-diameter implants and high-load areas, reducing the demand for bone incremental surgery, improving the fatigue resistance of the implant, reducing production costs, and realizing domestic substitution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614919A_ABST
    Figure CN119614919A_ABST
Patent Text Reader

Abstract

The invention provides a titanium-zirconium alloy wire for a high-strength annealed implant and a processing method of the titanium-zirconium alloy wire, and belongs to the technical field of titanium-zirconium alloy wire processing. According to the titanium-zirconium alloy wire for the high-strength annealed implant, the titanium-zirconium alloy wire for the high-strength annealed implant is prepared by adopting deformation distribution combining three times of VAR smelting, roller die hot drawing and cold drawing and a specific heat treatment process, the room-temperature tensile property is stable, the consistency is good, the tensile strength is larger than or equal to 1000 MPa, the hardness is larger than or equal to 270 HV, the grain size is smaller than or equal to 4 microns, and the hydrogen content of the finished wire is smaller than 0.002%. The titanium-zirconium alloy wire for the high-strength annealed implant, provided by the invention, has the characteristics of reducing the use of bone increment surgery and relieving the pain of a patient, and truly realizes localization in the field of new oral implant materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium-zirconium alloy wire processing, and in particular to a high-strength annealed titanium-zirconium alloy wire for implants and a processing method thereof. Background Art

[0002] Oral implants, also known as dental implants or artificial implants, are a component of dental implants. During the treatment process, they are surgically implanted into the upper and lower jaws of the patient's toothless area to replace lost or extracted tooth roots to support the upper restoration. After the dental implants and bone tissue grow firmly, the doctor will install a base on top, and finally install an artificial crown on top of the base to achieve the purpose of repairing missing teeth. Artificial implants can be made of a variety of materials. The raw materials for commonly used implants are pure titanium or titanium alloys. The market demand for dental implants is large, but the current price of dental implants is relatively high, and the target audience is mainly high-spending groups. Providing good solutions for many consumers who have rigid demands but cannot afford the high cost of implants is a current problem.

[0003] Titanium-zirconium alloy is an emerging implant material that combines titanium and zirconium into one, combining the advantages of both materials. The nominal composition of titanium-zirconium alloy implants is composed of 15% zirconium and 85% titanium, while pure titanium implants contain only titanium. The strength of pure titanium is between 500MPa-700MPa, while the strength of titanium-zirconium alloy is higher than 800MPa. Therefore, titanium-zirconium alloy can use smaller diameter implants to replace regular diameter implants of pure titanium materials. For patients with insufficient bone mass, bone augmentation surgery can be avoided in some cases. Titanium-zirconium alloy has higher biocompatibility than pure titanium, and its unique alloy composition helps reduce the occurrence of allergic reactions, shorten bone healing time, and improve the success rate of implant surgery. There is less dental bacteria attached to the surface of titanium-zirconium alloy implants, which can effectively promote bone tissue regeneration, increase bone height, improve bone bonding rate, and quickly shorten the healing cycle. In addition, titanium-zirconium alloy has certain advantages in aesthetics. Its alloy composition makes the color of the implant closer to natural teeth, which helps to improve the appearance after implantation. Titanium-zirconium alloy implants are suitable for the anterior teeth area or patients with higher requirements for oral aesthetics, and can obtain more natural and beautiful results.

[0004] Currently, the most widely used material in the field of medical implants is cold-worked pure titanium GR4B, but the material has insufficient mechanical strength and a relatively high risk of stress fatigue fracture. The life of dental implants is short and it is difficult to meet the clinical needs of narrow gum bones or anterior tooth implants. Summary of the invention

[0005] In view of this, the present invention provides a high-strength annealed titanium-zirconium alloy wire for implants and a processing method thereof. The high-strength annealed titanium-zirconium alloy wire for implants of the present invention has stable room temperature tensile properties, good consistency, tensile strength greater than or equal to 1000MPa, hardness greater than or equal to 270HV, grain size less than or equal to 4μm, and hydrogen content of the finished wire less than 0.002%, which can truly achieve high-quality and low-price domestic substitution of oral implant materials.

[0006] The present invention provides a method for processing high-strength annealed titanium-zirconium alloy wire for implants, comprising the following steps:

[0007] (1) Ingot smelting: The chemical composition is prepared according to the nominal composition of Ti15Zr, mixed evenly and pressed into electrodes, and then smelted into ingots through three VAR processes;

[0008] (2) Forging: The finished ingot is heated to 850-1000℃ and then forged twice to be deformed into a square billet;

[0009] (3) Rolling: The billet is heated to the α+β two-phase region and then hot-rolled to deform into a bar billet;

[0010] (4) Roller die hot drawing: The hot rolled polished material is drawn through a hot roller die for multiple times to the required specifications;

[0011] The roller die hot drawing parameters are as follows: the temperature is not higher than 750°C, the roller die speed is controlled at 4-8m / min, the deformation is controlled at 0.5-1.0mm / die, and the temperature is reduced by 10°C every two die times;

[0012] (5) Roller die cold drawing: Use a cold roller die to draw until the diameter is 30% larger than the final product size;

[0013] The roller die cold drawing parameters are as follows: roller die speed 3-5m / min, deformation control 0.3-0.5mm / die, total deformation control 35%-45%, wire ovality control ±0.03mm;

[0014] (6) Heat treatment: annealing the coiled wire after being drawn by the roller die;

[0015] (7) Car lights;

[0016] (8) Straightening and cutting;

[0017] (9) Polishing.

[0018] Preferably, the raw materials in step (1) are nuclear grade zirconium sponge, titanium dioxide, 0 / 0A grade titanium sponge, wherein the oxygen content is not more than 0.30%.

[0019] Preferably, in step (1), the first smelting parameters are: current 8-10KA, melting voltage 28-32V, DC arc stabilization 4-8A, and melting vacuum less than 10Pa; the second smelting parameters are: current 10-14KA, melting voltage 28-32V, DC arc stabilization 5-10A, and melting vacuum less than 3.0Pa; the third smelting parameters are: current 14-18KA, melting voltage 30-35V, AC arc stabilization ±55G, melting vacuum less than 0.1Pa, and hot capping for not less than 110min.

[0020] Preferably, when the diameter of the finished ingot in step (2) is greater than 400 mm, the finished ingot is preheated before forging, and the preheating parameters are: heating to 800-850° C. in an electric furnace and keeping warm for 90-120 min.

[0021] Preferably, the hot rolling temperature in step (3) is controlled at 750-850°C.

[0022] Preferably, the annealing treatment parameters in step (6) are: heating to 550-650° C., keeping warm for 40-60 min, and air cooling.

[0023] Preferably, the polishing parameters in step (7) are as follows: polishing thickness is controlled at 0.03-0.08 mm, and ellipticity is ≤0.01 mm.

[0024] Preferably, in step (8), the finished wire is obtained after straightening and cutting, and the straightness of the finished wire is ≤0.2 mm / m.

[0025] The present invention also provides a high-strength annealed titanium-zirconium alloy wire for implants obtained according to the processing method.

[0026] Preferably, the H content of the high-strength annealed titanium-zirconium alloy wire for implants does not exceed 0.002wt%, the strength index is not less than 1000MPa, and the grain size is less than or equal to 4μm.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The high-strength annealed titanium-zirconium alloy wire for implants prepared by the present invention through three-stage VAR melting, deformation distribution combined with roller die hot drawing and cold drawing, and a specific heat treatment process has stable room temperature tensile properties, good consistency, a tensile strength greater than or equal to 1000MPa, a hardness greater than or equal to 270HV, a grain size less than or equal to 4μm, and a hydrogen content of the finished wire less than 0.002%.

[0029] The processing method of the high-strength annealed titanium-zirconium alloy wire for implants provided by the present invention can realize the industrial production of fine-grained, high-strength, high-plasticity ton-level products with a diameter of less than 4 μm.

[0030] The high-strength annealed titanium-zirconium alloy wire for implants described in the present invention has excellent mechanical properties and is suitable for the clinical needs of narrow-diameter implants (<3.5mm) with insufficient bone mass, as well as implant sites with large occlusal forces. It meets the fatigue test requirements of a maximum load of 300N, a frequency of 15Hz, and 5 million cycles. It also has the characteristics of reducing the use of bone augmentation surgery and alleviating the pain of patients, and can truly achieve localization in the field of new materials for oral implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a fatigue test curve of an implant made of a φ6.0 mm titanium-zirconium alloy wire prepared in Example 1 of the present invention, subjected to 5 million cycles of cyclic loading at a load of 300 N and a frequency of 15 Hz;

[0032] Figure 2 This is a fatigue test curve of an implant made of a φ6.0 mm titanium-zirconium alloy wire prepared in Example 2 of the present invention, subjected to 5 million cycles of cyclic loading at a load of 300 N and a frequency of 15 Hz;

[0033] Figure 3 This is a fatigue test curve of an implant made of a φ6.0 mm titanium-zirconium alloy wire prepared in Example 3 of the present invention, subjected to 5 million cycles of cyclic loading at a load of 300 N and a frequency of 15 Hz;

[0034] Figure 4 This is a microstructure diagram of the titanium-zirconium alloy wire prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The present invention provides a method for processing high-strength annealed titanium-zirconium alloy wire for implants, comprising the following steps:

[0036] (1) Ingot smelting: The chemical composition is prepared according to the nominal composition of Ti15Zr, mixed evenly and pressed into electrodes, and then smelted into ingots through three VAR processes;

[0037] (2) Forging: The finished ingot is heated to 850-1000℃ and then forged twice to be deformed into a square billet;

[0038] (3) Rolling: The billet is heated to the α+β two-phase region and then hot-rolled to deform into a bar billet;

[0039] (4) Roller die hot drawing: The hot rolled polished material is drawn through a hot roller die for multiple times to the required specifications;

[0040] The roller die hot drawing parameters are as follows: the temperature is not higher than 750°C, the roller die speed is controlled at 4-8m / min, the deformation is controlled at 0.5-1.0mm / die, and the temperature is reduced by 10°C every two die times;

[0041] (5) Roller die cold drawing: Use a cold roller die to draw until the diameter is 30% larger than the final product size;

[0042] The roller die cold drawing parameters are as follows: roller die speed 3-5m / min, deformation control 0.3-0.5mm / die, total deformation control 35%-45%, wire ovality control ±0.03mm;

[0043] (6) Heat treatment: annealing the coiled wire after being drawn by the roller die;

[0044] (7) Car lights;

[0045] (8) Straightening and cutting;

[0046] (9) Polishing.

[0047] In some embodiments, the raw materials in step (1) are selected from nuclear grade zirconium sponge, titanium dioxide, and 0 / 0A grade titanium sponge, wherein the oxygen content is not greater than 0.30%.

[0048] In some embodiments, the first melting parameters in step (1) are: current 8-10KA, melting voltage 28-32V, DC arc stabilization 4-8A, and melting vacuum less than 10Pa; the second melting parameters are: current 10-14KA, melting voltage 28-32V, DC arc stabilization 5-10A, and melting vacuum less than 3.0Pa; the third melting parameters are: current 14-18KA, melting voltage 30-35V, AC arc stabilization ±55G, melting vacuum less than 0.1Pa, and thermal capping is not less than 110min. The present invention does not strictly limit the thermal capping time. Generally speaking, the longer the thermal capping time, the better. Preferably, the thermal capping time is 110-150min.

[0049] Further preferably, the first melting parameters are: current 8KA, melting voltage 28V, DC arc stabilization 5A, melting vacuum degree less than 10Pa; the second melting parameters are: current 12KA, melting voltage 30V, DC arc stabilization 8A, melting vacuum degree less than 3.0Pa; the third melting parameters are: current 17KA, melting voltage 32V, AC arc stabilization ±55G, melting vacuum degree less than 0.1Pa, and hot capping for 120min.

[0050] In some embodiments, when the diameter of the finished ingot in step (2) is greater than 400 mm, the finished ingot is preheated before forging, and the preheating parameters are: heated to 800-850°C in an electric furnace and kept warm for 90-120 minutes. When the ingot diameter is less than 400 mm, no preheating is required. The present invention does not strictly limit the ingot diameter. Generally speaking, the larger the ingot diameter, the longer the preheating time is, to ensure that the grains are fully broken during the forging process.

[0051] In some embodiments, the conditions of the two-fire forging in step (2) are as follows: the first fire forging is kept at 800°C for 120 minutes, then the temperature is raised to 980°C and kept for 330 minutes, and three-upsetting and three-drawing forging is adopted; the second fire forging is kept at 860°C for 180 minutes.

[0052] In some embodiments, the hot rolling temperature in step (3) is controlled at 750-850° C. More preferably, the hot rolling is performed in two steps, wherein the first step is performed at 830° C. for 90 min, and the second step is performed at 780° C. for 60 min.

[0053] In some embodiments, the roller die hot drawing parameters in step (4) are as follows: initial temperature 750°C, roller die speed controlled at 8m / min, deformation controlled at 1.0mm / die, and reduced by 10°C every two dies.

[0054] In some embodiments, the roller die hot drawing parameters in step (4) are as follows: initial temperature 750°C, roller die speed controlled at 7m / min, deformation controlled at 0.8mm / die, and reduced by 10°C every two dies.

[0055] In some embodiments, the roller die hot drawing parameters in step (4) are as follows: initial temperature 750°C, roller die speed controlled at 6m / min, deformation controlled at 0.6mm / die, and reduced by 10°C every two dies.

[0056] In some embodiments, the roller die cold drawing parameters in step (5) are as follows: roller die speed 5 m / min, deformation amount controlled at 0.5 mm / die, total deformation amount controlled at 41%, and wire ovality controlled at ±0.03 mm.

[0057] In some embodiments, the roller die cold drawing parameters in step (5) are as follows: roller die speed 4 m / min, deformation amount controlled at 0.4 mm / die, total deformation amount controlled at 43%, and wire ovality controlled at ±0.03 mm.

[0058] In some embodiments, the roller die cold drawing parameters in step (5) are as follows: roller die speed 3 m / min, deformation amount controlled at 0.3 mm / die, total deformation amount controlled at 45%, and wire ovality controlled at ±0.03 mm.

[0059] In some embodiments, the annealing treatment parameters of step (6) are: heating to 550-650°C, keeping warm for 40-60 minutes, and air cooling. More preferably, the annealing treatment parameters of step (6) are: heating to 600°C, keeping warm for 60 minutes.

[0060] In some embodiments, the polishing parameters in step (7) are as follows: polishing thickness is controlled at 0.03-0.08 mm, and ellipticity is ≤ 0.01 mm.

[0061] In some embodiments, the finished wire is obtained after straightening and cutting in step (8), and the straightness of the finished wire is ≤0.2 mm / m.

[0062] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0063] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0064] The method for testing the performance of the alloy wire in the following embodiments is as follows:

[0065] Mechanical properties testing is carried out in accordance with the standard GB / T 228.1-2010; microstructure testing is carried out in accordance with the standard GB / T5168-2020; grain size rating is carried out in accordance with the standard GB / T 6394-2017; hardness testing is carried out in accordance with the standard ASTM E92-2017.

[0066] Example 1

[0067] A method for processing high-strength annealed titanium-zirconium alloy wire for implants, comprising the following steps:

[0068] (1) Ingot smelting: Use "0-grade" titanium sponge, "nuclear grade 1" zirconium sponge and titanium dioxide powder as raw materials, prepare according to the nominal composition of Ti15Zr, mix evenly and press into electrodes, and smelt the obtained electrode rods in a vacuum consumable melting furnace for 3 times. The first smelting parameters: current 8KA, melting voltage 28V, DC arc stabilization 5A, melting vacuum less than 10pa; the second smelting parameters: current 12KA, melting voltage 30V, DC arc stabilization 8A, melting vacuum less than 3.0pa; the third smelting parameters: current 17KA, melting voltage 32V, AC arc stabilization ±55G, melting vacuum less than 0.1pa, hot capping 120min, and obtain a Φ560×L mm ingot;

[0069] The chemical composition of the ingot was tested and the results are shown in Table 1.

[0070] Table 1

[0071]

[0072] The (α+β / β) phase transition point is 895°C as measured by metallographic method, and the H element is the test result of the finished product.

[0073] (2) Forging: The smelted ingot is sawed to remove the riser and bottom, and then polished to obtain a finished ingot. The finished ingot is forged in two fires. The first fire is 800°C and kept warm for 120 min, then the temperature is raised to 980°C and kept warm for 330 min, and three-upsetting and three-drawing forging is adopted; the second fire is 860°C and kept warm for 180 min, and the billet is forged into a square billet of 150*150*Lmm by drawing;

[0074] (3) Rolling: The forged billet is rolled in two rounds. The first round is rolled at a temperature of 830°C for 90 minutes and rolled to φ55 mm. The second round is rolled at a temperature of 780°C for 60 minutes and rolled to φ12 mm.

[0075] (4) Roller die hot drawing: The rolled bar blank is polished and drawn through a hot roller die to φ8.3 mm. The roller die speed is controlled at 8 m / min, the deformation is controlled at 1.0 mm / die, and the initial temperature of the hot roller die is 750°C, which is reduced by 10°C every two dies;

[0076] (5) Roller die cold drawing: The hot roller die batch material is roller die cold drawn to φ6.4mm, the roller die speed is 5m / min, the deformation is controlled at 0.5mm / die, the total deformation is controlled at 41%, and the closing is φ500mm;

[0077] (6) Heat treatment: The finished material is heat treated, and the heat treatment system is heating to 600°C, keeping warm for 60 minutes, and air cooling to room temperature;

[0078] (7) Polishing: Polish the annealed wire coil Φ6.4*L mm to remove the oxide scale to Φ6.30*L;

[0079] (8) Straightening and cutting: Straightening and cutting of the lathe wire, straightness ≤ 0.2 mm / m, fixed cutting length L = 3000 mm;

[0080] (9) Polishing: The cut-length material is polished to obtain titanium-zirconium alloy wire φ6.0 (-0.002, -0.012)*Lmm.

[0081] The implant made of φ6.0 mm titanium-zirconium alloy wire prepared in Example 1 was subjected to a fatigue test at a load of 300 N and a frequency of 15 Hz for 5 million cycles according to the requirements of YY / T0521-2018 "Dynamic fatigue test of intraosseous dental implants in dentistry". The fatigue test conclusion: no failure, the test results are as follows Figure 1 .

[0082] The mechanical properties, grain size and hardness of the titanium-zirconium alloy wire prepared in Example 1 were tested, and the results are shown in Table 2.

[0083] Table 2

[0084]

[0085] Example 2

[0086] Steps (1) to (3) of this embodiment are the same as those of Embodiment 1, and the remaining steps are as follows:

[0087] (4) Roller die hot drawing: The rolled bar blank is polished and drawn through a hot roller die to φ7.0 mm. The roller die speed is controlled at 7 m / min, the deformation is controlled at 0.8 mm / die, the temperature is not higher than 750°C, and it is reduced by 10°C every two dies;

[0088] (5) Roller die cold drawing: The hot roller die batch material is roller die cold drawn to φ5.3mm, the roller die speed is 4m / min, the deformation is controlled at 0.4mm / die, the total deformation is controlled at 43%, and the closing is φ500mm;

[0089] (6) Heat treatment: The finished material is heat treated, and the heat treatment system is heating to 600°C, keeping warm for 60 minutes, and air cooling to room temperature;

[0090] (7) Polishing: Polish the annealed wire coil Φ5.3*L mm to remove the oxide scale to Φ5.20*L;

[0091] (8) Straightening and cutting: Straightening and cutting of the lathe wire, straightness ≤ 0.2 mm / m, fixed cutting length L = 3000 mm;

[0092] (9) Polishing: The cut-length material is polished to obtain titanium-zirconium alloy wire φ5.0 (-0.002, -0.012)*Lmm.

[0093] The implant made of φ5.0 mm titanium-zirconium alloy wire prepared in Example 2 was subjected to a fatigue test at a load of 300 N and a frequency of 15 Hz for 5 million cycles according to the requirements of YY / T0521-2018 "Dynamic fatigue test of intraosseous dental implants in dentistry". The fatigue test conclusion: no failure, the test results are as follows Figure 2 .

[0094] The mechanical properties, grain size and hardness of the titanium-zirconium alloy wire prepared in Example 2 were tested, and the results are shown in Table 3.

[0095] Table 3

[0096]

[0097] Example 3

[0098] Steps (1) to (3) of this embodiment are the same as those of Embodiment 1, and the remaining steps are as follows:

[0099] (4) Roller die hot drawing: The rolled bar blank is polished and drawn to φ5.9 mm through a hot roller die. The roller die speed is controlled at 6 m / min, the deformation is controlled at 0.6 mm / die, the temperature is not higher than 750°C, and the temperature is reduced by 10°C every two dies;

[0100] (5) Roller die cold drawing: The hot roller die batch material is roller die cold drawn to φ4.3mm, the roller die speed is 3m / min, the deformation is controlled at 0.3mm / die, the total deformation is controlled at 45%, and the closing is φ500mm;

[0101] (6) Heat treatment: The finished material is heat treated, and the heat treatment system is heating to 600°C, keeping warm for 60 minutes, and air cooling to room temperature;

[0102] (7) Polishing: Polish the annealed wire coil Φ4.3*L mm to remove the oxide scale to Φ4.20*L;

[0103] (8) Straightening and cutting: The lathe wire is cold straightened and cut, with a straightness of ≤0.2mm / m and a fixed cutting length of L=3000mm;

[0104] (9) Polishing: The cut-length material is polished to obtain titanium-zirconium alloy wire φ4.0 (-0.002, -0.012)*Lmm.

[0105] The implant made of φ4.0 mm titanium-zirconium alloy wire prepared in Example 3 was subjected to a fatigue test at a load of 300 N and a frequency of 15 Hz for 5 million cycles according to the requirements of YY / T0521-2018 "Dynamic fatigue test of intraosseous dental implants in dentistry". The fatigue test conclusion: no failure, the test results are as follows Figure 3 .

[0106] The mechanical properties, grain size and hardness of the titanium-zirconium alloy wire prepared in Example 3 were tested, and the results are shown in Table 4.

[0107] Table 4

[0108]

[0109] Comparative Example 1

[0110] The steps (1) to (3) of this comparative example are the same as those of Example 1, and the remaining steps are as follows:

[0111] (4) Hot drawing: The rod blank is heated, and the heating temperature is gradually reduced from 780° C. to 720° C. The drawing speed is 2.0 m / min, and the hot drawing deformation is controlled at 0.5 mm / mold, and the rod blank is drawn to a specification of Φ6.4 mm;

[0112] (5) Cutting: fixed cutting length L = 3000mm;

[0113] (6) Heat treatment: The hot drawn wire material after cutting is annealed. The heat treatment procedure is heating to 600°C, keeping the temperature for 60 minutes, and air cooling to room temperature.

[0114] (7) Electrical straightening: the counterweight is set to 30 kg and the current is set to 180 A;

[0115] (8) Polishing: The grinding process uses a centerless grinder to obtain titanium-zirconium alloy wire φ6.0 (-0.002, -0.012)*Lmm.

[0116] The mechanical properties, grain size and hardness of the titanium-zirconium alloy wire prepared in “Comparative Example 1” were tested, and the results are shown in Table 5.

[0117] Table 5

[0118]

[0119]

[0120] Comparative Example 2

[0121] The difference between the grades of this comparative example and Example 1 is that the alloy elements in the titanium sponge are set according to the composition ratio of TA4G in GB / T 3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions". "Grade 0" titanium sponge, ferrotitanium alloy and titanium dioxide powder are selected as raw materials.

[0122] The process difference between this comparative example and Example 1 is that: "Comparative Example 2" removes step 6 in "Example 1": closing heat treatment process, that is, "Comparative Example 2" adopts cold working process.

[0123] The chemical composition of the ingot was tested and the results are shown in Table 6.

[0124] Table 6

[0125] element O / % Fe / % C / % N / % H / % Standard range <0.40 <0.50 <0.08 <0.05 <0.015 Detection value 0.22 0.33 0.006 0.005 0.0025

[0126] The (α+β / β) phase transition point is 905°C as measured by metallographic method, and the H element is the test result of the finished product.

[0127] The mechanical properties, grain size and hardness of the alloy wire prepared in “Comparative Example 2” were tested, and the results are shown in Table 7.

[0128] Table 7

[0129]

[0130] From the analysis, it can be seen that the comparative example 1 and the embodiment adopt different drawing processes. The drawing speed of the embodiment is increased by more than 2.5 times, and the production efficiency of the straightening process is increased by more than 2 times, which is more conducive to mass production and truly realizes the market competition model of reducing costs and increasing efficiency.

[0131] The degree of deformation uniformity of roller die drawing in Examples 1-3 is better than that of hole die drawing in Comparative Example 1, and the grain size is refined from 10 μm to within 4 μm.

[0132] The strength index of Examples 1-3 is improved by more than 12% compared with that of Comparative Example 1, and Examples 1-3 all meet the market demand for tensile strength greater than 1000 MPa and elongation greater than 15%. At the same time, the high-strength titanium-zirconium alloy wire also meets the clinical demand for narrow diameter implants (<3.5 mm).

[0133] Comparative Example 2 is the conventional production model of Grade 4 pure titanium implants in the current domestic medical industry. The elastic modulus of the embodiment is reduced by more than 9% compared with that of Comparative Example 2, further reducing the risk of "stress shielding" caused by the mismatch between the titanium-zirconium alloy implant and the human bone tissue. The strength index is increased by more than 28% compared with the comparative example, and the grain size is much lower than that of the comparative example, truly realizing the domestic substitution of pure titanium for oral implant materials.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for processing high-strength annealed titanium-zirconium alloy wire for implants, characterized in that: The following steps are involved: (1) Ingot smelting: The chemical composition is prepared according to the nominal composition of Ti15Zr, mixed evenly and pressed into electrodes, and then smelted into ingots through three VAR processes; (2) Forging: The finished ingot is heated to 850-1000℃ and then forged twice to be deformed into a square billet; (3) Rolling: The billet is heated to the α+β two-phase region and then hot-rolled to deform into a bar billet; (4) Roller die hot drawing: The hot rolled polished material is drawn through a hot roller die for multiple times to the required specifications; The roller die hot drawing parameters are as follows: the temperature is not higher than 750°C, the roller die speed is controlled at 4-8m / min, the deformation is controlled at 0.5-1.0mm / die, and the temperature is reduced by 10°C every two die times; (5) Roller die cold drawing: Use a cold roller die to draw until the diameter is 30% larger than the final product size; The roller die cold drawing parameters are as follows: roller die speed 3-5m / min, deformation control 0.3-0.5mm / die, total deformation control 35%-45%, wire ovality control ±0.03mm; (6) Heat treatment: annealing the coiled wire after being drawn by the roller die; (7) Car lights; (8) Straightening and cutting; (9) Polishing.

2. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: The raw materials in step (1) are nuclear grade zirconium sponge, titanium dioxide, and 0 / 0A grade titanium sponge, wherein the oxygen content is not more than 0.30%.

3. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: The first smelting parameters in step (1) are: current 8-10KA, melting voltage 28-32V, DC arc stabilization 4-8A, and melting vacuum less than 10Pa; the second smelting parameters are: current 10-14KA, melting voltage 28-32V, DC arc stabilization 5-10A, and melting vacuum less than 3.0Pa; the third smelting parameters are: current 14-18KA, melting voltage 30-35V, AC arc stabilization ±55G, melting vacuum less than 0.1Pa, and hot capping for not less than 110min.

4. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: When the diameter of the finished ingot in step (2) is greater than 400 mm, the finished ingot is preheated before forging, and the preheating parameters are: heating to 800-850° C. in an electric furnace and keeping warm for 90-120 minutes.

5. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: The hot rolling temperature in step (3) is controlled at 750-850°C.

6. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: The annealing treatment parameters of step (6) are: heating to 550-650° C., keeping warm for 40-60 minutes, and air cooling.

7. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: The polishing parameters of step (7) are as follows: the polishing thickness is controlled at 0.03-0.08 mm, and the ovality is ≤0.01 mm.

8. The method for processing high-strength annealed titanium-zirconium alloy wire for implants according to claim 1, characterized in that: In step (8), the finished wire is obtained after straightening and cutting, and the straightness of the finished wire is ≤0.2 mm / m.

9. A high-strength annealed titanium-zirconium alloy wire for implants obtained according to the processing method according to any one of claims 1 to 8.

10. The high-strength annealed titanium-zirconium alloy wire for implants according to claim 9, characterized in that: The H content in the titanium-zirconium alloy wire does not exceed 0.002wt%, the strength index is not less than 1000MPa, and the grain size is less than or equal to 4μm.